Classroom Scaffolding: Teaching Reading and Writing in English - Widia Resdiana (Bandar Lampung University (UBL), 2013)
One of the main concerns in Education of Indonesia is Literary Writing and Reading in English, as stated in Government Regulation No. 23 Year 2006. The Curriculum of English Literacy in Indonesia has been developed and teachers require more models in the teaching of English reading and writing in order to successfully increase students’ skills in reading and writing. One of the approaches is Genre Based, which has been also developed to Learning to Read: Reading to Learn (LRRL) program by David Rose. This program has successfully increased students’ literary skills at twice the expected rate with integrating teaching of high level skills in reading and writing with normal classroom program across the curriculum in Australia. This paper aims, firstly, to describe the first important stage of the program in a study conducted in a vocational high school in Bandung, Indonesia. The description deals with the theory of scaffolding in classroom, which is one of the conceptual frameworks of Reading to Learn strategy, where learning with the support of teacher will be more successful than learning independently. Secondly, it also aims to show how the stage was conducted in Indonesian context, as in reading materials and points of view.The result of this research shows thatsuch program can also give significant contributions to improve students’ skill in reading and writing. In addition, scaffolding plays the most important roles in preparing students to comprehend reading and practicing writing, so that teachers should have more understanding about scaffolding.